Compensation Committee Composition as a Determinant of Ceo Compensation - Daily, Catherine M.; Johnson, Jonathan L.; Ellstrand, Alan E.; Dalton, Dan R. (Academy of Management Journal, 1998)
Extant research examining the relationship between a firm's board and its CEO's compensation has focused primarily on the composition of the board-at-large. However, it may be the nature of the com...